Biocementation and bioclogging of sand using improved MICP techniques - Yang, Yang (Nanyang Technological University, 2021)
Studies on the use of Microbially Induced Carbonate Precipitation (MICP) processes to improve the mechanical properties of soil have gained overwhelming attention in recent years. However, there are still many limitations in the current MICP based soil improvement techniques. These include the cost, effectiveness, reliability, and environmental effects of the methods for field applications. In this study, various improvements to the MICP process were made in order to optimize the MICP based soil improvement techniques and improve the performance of biocementation. The present study was conducted by combining the knowledge of hydrology, microbiology, and soil mechanics to enable the MICP techniques to be simpler, more economical, and more efficient. Element tests using small cylindrical samples and model tests of different scales were carried out. The engineering properties of the biocemented sand were assessed using unconfined compression tests, three points loading tests, and permeability tests. The microstructure of the biotreated soil was examined using the Scanning Electron Microscopy together with x-ray diffraction. This thesis presents the studies that lead to the following original contributions. Firstly, a method to produce enriched urease producing bacteria from wastewater activated sludge was developed and the bacteria produced using this method could produce the same level of biocementation effect for sand. Thus, a bacteria cultivation method under non-sterile conditions has been established to enable large scale and cost-effective production of biomass for real project applications. Secondly, an improved one-phase-low-pH injection method using CH3COOH for acidification was developed to allow longer lag time to prevent premature bioclogging and achieve higher uniformity of calcium carbonate precipitation in soil. The results of model tests have shown improved performance using the proposed injection method. Thirdly, a method to use biolurry to reduce the permeability of sand to the level of 10-9 m/s was developed. This method could simplify the construction process by reducing the number of treatment involved, improve the productivity by shortening the construction time and enhance the reliability of the method. The effectiveness of this method for seepage control in sand was verified using a model test. Finally, a method to combine the reactive magnesia oxide and MICP process was also developed to allow sand, gravel, or other types of soil to be treated through mixing. This method allows the carbonation of reactive magnesia cement through a microbial process to allow soil to gain strength quickly. The testing data show that by using 8% of reactive magnesia cement (RMC) and 6M of urea at a water content of 0.2, an unconfined compressive strength of 2.3 MPa could be achieved for clean sand through one time mixing. Recommendations for future studies were also made.